2006
DOI: 10.1590/s0102-86502006000900008
|View full text |Cite
|
Sign up to set email alerts
|

Efeito do extrato hidroalcoólico de Aroeira (Schinus terebinthifolius Raddi) na cicatrização de anastomoses colônicas: estudo experimental em ratos

Abstract: RESUMO Introdução:A cicatrização é evento biológico complexo envolvendo inflamação, quimiotaxia, proliferação celular, diferenciação e remodelação. Na medicina popular brasileira, utiliza-se a Aroeira para tratar as mais diversas situações patológicas No Estado do Maranhão -Brasil, a Aroeira é extensivamente utilizada no tratamento de afecções do aparelho respiratório, digestivo e ginecológico. As anastomoses intestinais sempre foram motivo de preocupação para cirurgiões e constituem, até hoje assunto polêmico… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0
9

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 12 publications
0
7
0
9
Order By: Relevance
“…Actions anti-inflammatory and antiseptic for treatment of wounds, urinary, and respiratory infections are listed as medicinal properties popularly known [19]. Studies showed antimicrobial activity [15, 18, 2024], antifungal activity [25, 26], as antioxidant [15, 27], and antitumor [18, 28]. Despite its importance, there are a few records about the endophytic community in this plant.…”
Section: Introductionmentioning
confidence: 99%
“…Actions anti-inflammatory and antiseptic for treatment of wounds, urinary, and respiratory infections are listed as medicinal properties popularly known [19]. Studies showed antimicrobial activity [15, 18, 2024], antifungal activity [25, 26], as antioxidant [15, 27], and antitumor [18, 28]. Despite its importance, there are a few records about the endophytic community in this plant.…”
Section: Introductionmentioning
confidence: 99%
“…in a dose of 0.1 g/kg had a positive effect on the healing process of anastomoses of the colon (Coutinho et al, 2006), on healing surgical wounds in the bladder (Lucena et al, 2006) and via percutaneous route, on the back wounds of rats (Castelo-Branco Neto et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, studies on the composition of plant parts, isolated compounds such as: essential oils, flavonoids, fractions enriched of flavonoids, Shinol (flavonoid) and masticadienoic acid, biflavonoids isolated and triterpenes. Have been studied the morphology and anatomy of the seed, barks and leaves, chemical and microscopic examination of the plant, barks development and fruits development, even clinical drug trials (phase I) of an herbal compound (Schinus, Plectranthus and Eucalyptus) 1,3,4,5,7,8,9,10,11,15,18,19,20,21,23,25,26,28,30,31,32,33,34 .…”
mentioning
confidence: 99%